Birth month and infant gross motor development: Results from the Japan Environment and Children's Study (JECS). - Kahoko Yasumitsu-Lovell (Public Library of Science (PLoS), 2021)
The association between birth month and neurodevelopmental or psychiatric disorders has been investigated in a number of previous studies; however, the results have been inconsistent. This study investigated the association between birth month and child gross motor development at 6 and 12 months of age in a large cohort of infants (n = 72,203) participating in the Japan Environment and Children's Study (JECS). Gross motor development was assessed using the Ages and Stages Questionnaire (ASQ-3). At 6 months and 12 months, 20.7% and 14.2%, respectively, had ASQ-3 indications of gross motor problems. Birth month was strongly associated with gross motor development at both time points, particularly at 6 months. Summer-born infants had the worst outcomes at both 6 months and 12 months of age. This outcome applied to the ASQ-3 score itself and to the adjusted Relative Risk (aRR), with the highest aRRs (relative to January-born) among August-born (aRR 2.51; 95%CI 2.27-2.78 at 6 months), and June-born (aRR 1.84; 95%CI 1.63-2.09 at 12 months). Boys had better scores than girls both at 6 and 12 months of age. We speculate that seasonal factors-such as maternal vitamin D deficiency and influenza infection-affecting the fetus in early pregnancy might account for the findings.